Grammatical Features in the Introduction Section of English Undergraduate Thesis - Sari, Fenti Pratama; Yunita, Wisma; Maisarah, Ira (Linguistic, English Education and Art (LEEA) Journal, 2023)
This research aimed to find the grammatical features; (1) the total of tenses (present tense, past tense, and present perfect tense), (2) voice forms identification in the thesis introduction section of English Undergraduate. This research used quantitative method. The checklist and documentation are used as the instruments. The corpus of this research used were 20 introduction section of English Undergraduate thesis. The result reveals; first, the students most often used simple present tense with the total of 945, the total of simple past tense was 306, the present perfect tense showed the least appearance with the total 34. Second, the active form is the most often appears in the introduction section of the students’ theses which happened 1044 times meanwhile the total use of passive voice was 243. In conclusion, this research highlights grammatical features that are commonly used in the introduction section of undergraduate thesis; three tenses include simple present tense, simple past tense, and present perfect tense; voice forms that cover active form and passive form. Furthermore, the use of tenses types and voice forms are influenced by the context of idea expressed and functions of tenses and voice forms. As suggestion, undergraduate students are suggested to follow standards and trends in grammatical features used in writing the introduction section. Keywords: Grammatical Features, Introduction Section, Undergraduate Thesis